The impact of traditional mind–body exercises on pulmonary function, exercise capacity, and quality of life in patients with lung cancer: a systematic review and meta-analysis - Wu, Mingqi; Zhang, Sidi; Zhang, Hongka; Yin, Yijun; Wang, Shiyun; Li, Weiwei; Xiao, Jing; Tang, Zhanying (Frontiers in Oncology, 2025)
BackgroundA systematic evaluation of the clinical effects of mind-body traditional Chinese exercises (Qigong, Taichi, Baduanjin, Liuzijue and Wuqinxi) lung cancer patients.MethodsSystematic searches of PubMed, Embase, Cochrane Library, Web of Science and China Knowledge Network (CNKI), Wan fang, China Biology Medicine disc (CBM), and VIP were performed from the time of library construction to August 20, 2025. Lung cancer patients were included in the study, and the interventions were Qigong, Taichi, Baduanjin, Liuzijue or Wuqinxi, and the control group was conventional treatment or other non-exercise interventions. Meta-analysis was performed using Stata 15.Results22 randomized controlled studies involving 1827 patients including, meta-analysis results suggested that mind-body traditional Chinese exercises were able to reduce anxiety scores [SMD=-1.05, 95%CI (- 1.34, -0.76)], depression scores [SMD=-1.05, 95%CI (- 1.26, -0.82)], PSQI [SMD=-0.67, 95%CI (-1.17, -0.17)] and increase 6MWT [WMD = 31.24, 95%CI (19.54, 42.95)], quality of life scores [SMD = 0.85, 95%CI (0.36, 1.34)], FEV1 [WMD = 0.14, 95%CI (0.06, 0.23)],FVC [WMD = 0.08, 95%CI (0.02, 0.15)] in lung cancer patients.ConclusionIn this study, the results showed that the mind-body traditional Chinese exercises maybe significantly improve the patients’ anxiety, depression, sleep quality, exercise capacity, lung function and quality of life.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/, identifier CRD420251127148.